1992
DOI: 10.1128/iai.60.10.4221-4229.1992
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 58-kilodalton cell surface fibrinogen-binding mannoprotein from Candida albicans

Abstract: Treatment of both yeast (blastoconidia) and hyphal (blastoconidia with germ tubes) cells of Candida albicans with 1-mercaptoethanol (1ME) releases a complex array of cell wall-bound proteins and glycoproteins. Analysis by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western immunoblotting with fibrinogen-anti-fibrinogen antibody allowed the identification of a 58-kDa mannoprotein (mp58) in both extracts which specifically interacts with human fibrinogen. Treatment of intact cells with low conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 44 publications
(53 reference statements)
9
82
1
Order By: Relevance
“…For example, C. albicans wall proteins of 37, 60, 62, 67, and 68 kDa have been observed to bind laminin [15,16]. These molecular masses are very similar to those of proteins reported to bind ¢brinogen [14], ¢bronectin [12], C3d [11,13], and iC3b [48]. Although there is some evidence that this multiplicity is due to protein glycosylation [48], it has not been demonstrated that these proteins are structurally related to each other.…”
Section: Discussionmentioning
confidence: 87%
“…For example, C. albicans wall proteins of 37, 60, 62, 67, and 68 kDa have been observed to bind laminin [15,16]. These molecular masses are very similar to those of proteins reported to bind ¢brinogen [14], ¢bronectin [12], C3d [11,13], and iC3b [48]. Although there is some evidence that this multiplicity is due to protein glycosylation [48], it has not been demonstrated that these proteins are structurally related to each other.…”
Section: Discussionmentioning
confidence: 87%
“…C. albicans clinical isolates from blood of patients with invasive candidiasis were propagated as blastoconidia in liquid synthetic minimal medium at 28³C, harvested, and stored at 4³C for 72^96 h (starvation period); starved blastoconidia were inoculated in fresh Lee medium and incubated for 6 h at 28³C to obtain cultures of blastoconidia or at 37³C for the formation of blastoconidia bearing germ tubes as reported previously [30,31]. Most blastoconidia from all clinical strains used were able to form germ tubes under these experimental conditions.…”
Section: Strains Used and Culture Conditionsmentioning
confidence: 99%
“…Protein and glycoprotein components of the walls were obtained from intact cells by treatment with Lmercaptoethanol (LME) [31,32]. Molecular species in the LME extracts were separated by SDS-PAGE, transferred to polyvinylidene di£uoride membranes (Millipore) and immunodetected with PAb anti-CA-GAPDH [5,6], as described [5,30,31].…”
Section: Preparation Of Cell Wall Extracts and Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of plasma and extracellular matrix proteins have been demonstrated to bind to C. albicans. These include fibrinogen [45], vitronectin [46], laminin [47], and entactin [48]. Whether or not these receptors prove to be involved in the adherence process remains to be demonstrated.…”
Section: C3d Receptor and Other Extracellular Matrix Protein Receptorsmentioning
confidence: 99%